2016
DOI: 10.4103/0973-1482.200746
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between periodontal disease and oral cancer risk: A meta-analysis

Abstract: Our present meta-analysis indicated that periodontal disease can increase the oral cancer risk by nearly 2-fold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 0 publications
1
38
0
3
Order By: Relevance
“…Different from all-cause death, the definite relevance between periodontal disease and cardiovascular mortality in CKD people is not observed in the present meta-analysis, which excludes the mechanism that elevated all-cause mortality is mediated by cardiovascular disease progression. A large number of publications have suggested that periodontal disease correlated significantly with death from various kinds of cancer [ 60 , 61 ], diabetes [ 62 ], and respiratory disease [ 63 , 64 ]. In addition, the study by Ruokonen also revealed that noncardiovascular systemic diseases, such as infection, and malignant disease were the main causes of death among CKD populations, which show significant association with periodontal disease [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different from all-cause death, the definite relevance between periodontal disease and cardiovascular mortality in CKD people is not observed in the present meta-analysis, which excludes the mechanism that elevated all-cause mortality is mediated by cardiovascular disease progression. A large number of publications have suggested that periodontal disease correlated significantly with death from various kinds of cancer [ 60 , 61 ], diabetes [ 62 ], and respiratory disease [ 63 , 64 ]. In addition, the study by Ruokonen also revealed that noncardiovascular systemic diseases, such as infection, and malignant disease were the main causes of death among CKD populations, which show significant association with periodontal disease [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…CP patients are at substantial risk for developing deadly oral cancers, 90% of which are recurrent OSCC having less than 50% survival rate 5 , 6 . It has been denoted that patients with CP are more susceptible to poorly differentiated OSCC than those without periodontitis, thus indicating the association of periodontal disease with the development as well as advancement of oral cancers 7 , 8 . A recent cohort study emphasizes the role of periodontal disease in incident cancer risk among postmenopausal women 9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation between HPV and OC is inconclusive mainly due to different subsites of the oral cavity being combined as a single entity in national reports [14, 15]. Finally, two independent meta-analyses correlated OC with processed meat consumption (RR  =  1.91, 95% CI (1.19–3.06)) and periodontal disease (OR = 3.21, 95% CI (2.25–4.16)) [16, 17]. …”
Section: Introductionmentioning
confidence: 99%